Blended Learning Models Using Moodle SPADA Unram to Enhance Student Critical Thinking PPKn Study Program FKIP University of Mataram - Ahmad Fauzan; Rispawati Rispawati; Lalu Sumardi (Jurnal Ilmiah Profesi Pendidikan, 2023)
This project aims to learn more about the usage of blended learning models using moodle Spada Unram to foster critical thinking among students enrolled in programs at Mataram's PPKn and FKIP universities. This type of investigation is quasi-experimental. There was no requirement for a group control because this study only involved one group and was a group experiment. Students participating in the PPKn FKIP University of Mataram study program may exhibit enhanced critical thinking if blended learning models with moodle Spada Unram are utilized. Students have watched the process of learning. Blended learning is a method of instruction that makes use of technology, specifically the internet and websites, to augment offline or face-to-face learning with online instruction. Due to the convenience of access offered, learning can assist in overcoming educational difficulties such as room class constraints, level presence lecturer class, and level presence student in the classroom.Blended Learning, Moodle, SPADA, UNRAM, and Critical Thinking are described.